2017
DOI: 10.1021/acs.inorgchem.6b02697
|View full text |Cite
|
Sign up to set email alerts
|

Germanium Compounds Containing Ge═E Double Bonds (E = S, Se, Te) as Single-Source Precursors for Germanium Chalcogenide Materials

Abstract: New germanium chalcogenide precursors, S═Ge(dmamp) (3), S═Ge(dmampS) (4), Se═Ge(dmamp) (5), Se═Ge(dmampS) (6), Te═Ge(dmamp) (7), and Te═Ge(dmampS) (8), were synthesized from Ge(dmamp) (1) and Ge(dmampS) (2) using sulfur, selenium, and tellurium powders (dmamp = 1-dimethylamino-2-methyl-2-propanolate, dmampS = 1-dimethylamino-2-methylpropane-2-thiolate). Complexes 1 and 2 were synthesized from metathesis reactions of GeCl·dioxane with 2 equiv of aminoalkoxide or aminothiolate ligands. Thermogravimetric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…As a caveat we note that 77 Se NMR chemical shifts of the comparatively much more abundant germaneselones with four‐ or five‐coordinated Ge IV lie in the broad range between ca. –464 and 1116 ppm, with no clear trend being apparent , . In fact, small structural changes may cause massive chemical shift differences, as is illustrated by a comparison of two homologous germaneselones of the type [(Me 3 Si)(2‐pyridyl) R C] 2 GeSe with pentacoordinate Ge IV : The 77 Se NMR signal is located at δ = –97.6 ppm for R = SiMe 3 and at δ = 1097.1 ppm for R = Ph.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a caveat we note that 77 Se NMR chemical shifts of the comparatively much more abundant germaneselones with four‐ or five‐coordinated Ge IV lie in the broad range between ca. –464 and 1116 ppm, with no clear trend being apparent , . In fact, small structural changes may cause massive chemical shift differences, as is illustrated by a comparison of two homologous germaneselones of the type [(Me 3 Si)(2‐pyridyl) R C] 2 GeSe with pentacoordinate Ge IV : The 77 Se NMR signal is located at δ = –97.6 ppm for R = SiMe 3 and at δ = 1097.1 ppm for R = Ph.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, small structural changes may cause massive chemical shift differences, as is illustrated by a comparison of two homologous germaneselones of the type [(Me 3 Si)(2‐pyridyl) R C] 2 GeSe with pentacoordinate Ge IV : The 77 Se NMR signal is located at δ = –97.6 ppm for R = SiMe 3 and at δ = 1097.1 ppm for R = Ph. [19e], [19g] A significant dissociation of [ 1Pr* Ge(μ‐Se)] 2 into the monomeric germaneselone 1Pr* GeSe in benzene solution was ruled out by the result of a molecular weight determination by cryoscopy in benzene.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al synthesised (R 2 GeTe) 3 (R = Et, Bu) (1) from the reaction of Li 2 Te and R 2 GeCl 2 , and thermal decomposition of the precursor in trioctylphosphine at 300°C resulted in rhombohedral GeTe, 38 while Kim et al showed that thermal decomposition of [Te = Ge(dmampS) 2 ] (2) in hexadecane at 270°C produced Te-rich rhombohedral Ge 40 Te 57 . 39 There is just one previous example of a single source CVD precursor for the deposition of GeTe thin films. Using [Ge{N(SiMe 2 CH 2 CH 2 Me 2 Si)} 2 ( i Pr)(Te i Pr)] (3) in NH 3 , Chen et al reported that GeTe film growth occurs between 280 and 400°C.…”
Section: Introductionmentioning
confidence: 99%
“…Germanium chalcogenides are interesting chemical species for optoelectronic modules due to the appropriate combination between the electron-accepting element Ge and an electron-donating element, such as Se or Te, because the size and energy levels of frontier orbitals should be close to each other (4p and 4p/5p) [1,2]. Therefore, organogermanium species that bear a chalcogen (Ch) moiety should be able to serve as building blocks for organic-inorganic hybrid materials that contain a Ge-Ch bond.…”
Section: Introductionmentioning
confidence: 99%